Screening for Gestational Diabetes; Can Apelin Help? - Salman, Dina A.; Hussein, Zina Abdullah; Eimad, Taif; Nori, Wassan (Current Women's Health Reviews, 2024)
Background: Gestational diabetes (GDM) is a pregnancy-related endocrinopathy. Its etiology is not well understood. Obesity and insulin resistance coexist in GDM. Apelin is an adipocytokine secreted by fatty cells and expressed in many organs; it can modulate blood glucose. According to research, apelin levels are higher in obese and type 2 diabetes patients. We aimed to examine the value of serum apelin as a reliable marker for GDM at 24-28 weeks of pregnancy. Methods: A case-control study recruited 120 pregnant women in an age range of 20-40 years with a singleton pregnancy at 24-28 weeks of pregnancy; all were matched in BMI and gestational age. They are divided into 2 groups: 60/120 GDM cases based on the International Association of Diabetes and Pregnancy and 60/120 matched controls at a gestational age of 24-28 weeks at Al-Yarmouk Teaching Hospital. Demographics data, serum biochemical permeates including HbA1c, fasting blood sugar (FBS), fasting insulin level, 1 h plasma glucose, and 2 h plasma glucose, following a 75-gram glucose loading, and a fasting insulin level were recorded. Results: None of the demographic criteria were significant between the two groups at P < 0.05. FBS, fasting insulin, OGTT-1 and 2 hours, HbA1c, and serum apelin were significantly higher in GDM cases with P < 0.0001. Pearson's correlations show that Apelin has a statistically significant correlation with BMI, FBS, fasting insulin, OGTT-1 and 2 hours, and HbA1c, with r = (0.34, 0.71, 0.65, 0.72, and 0.63) and P < 0.0001. ANOVA confirmed an insignificant effect of BMI centile on serum apelin, P < 0.072. ROC estimated the apelin cut-off at > 11.3 (ng/l), associated with 84% sensitivity and 100% specificity, P < 0.001. Conclusion: Strong and significant apelin correlations with parameters for screening GDM make it a valuable marker, especially when its levels are unaffected by body mass index. Further studies are recommended to unveil therapeutic avenues for apelin.
Keywords: blood glucose